A Comparative Study of Fifth Grade Mathematics Textbooks in Iranian and International Schools based on Critical Thinking Components - Morteza Samiee Zafarghandi; Aboutaleb Seadatee Shamir; Maryam Shamsolahi (Iranian Journal of Comparative Education, 2020)
The main goal of present study is to compare content of Fifth Grade mathematics textbooks of Iran and International schools based on critical thinking components. The research method was a comparative using content analysis approach and statistical population and sample included all Fifth-grade mathematics textbooks of primary school of Iran and two International Schools in Tehran. To collect data, the content analysis form based on the components of Lipman's critical thinking was used. To determine formal and content validity, the researchers have used perspective of five experienced math teachers of primary schools and three university professors in the field of curriculum. The reliability coefficient of the research instrument was determined using Holste formula and it was for Iran and International schools equal to 0.89 and 0.84. Data analysis also showed that the content of Iran and International math textbooks are active up to 73% and 88% respectively. The research findings show that in mathematics textbook of Iran, components of critical thinking are unbalanced, which means that attention is more on necessary components of critical thinking such as questioning. However, the components related to analysis ability and high levels of critical thinking have received less attention. According to the findings of the research, the authors of the mathematics textbooks in Iran are suggested to improve content of math book, to provide a suitable ground for cultivating critical thinking of pupils.